2000
DOI: 10.3171/jns.2000.92.2.0249
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of progressive or recurrent pediatric malignant supratentorial brain tumors with herpes simplex virus thymidine kinase gene vector—producer cells followed by intravenous ganciclovir administration

Abstract: This Phase I study demonstrates that in vivo gene therapy in which a replication-defective retroviral vector in murine vector-producing cells is delivered by brain injections can be performed with satisfactory safety in a select group of children with localized supratentorial brain tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2000
2000
2007
2007

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(14 citation statements)
references
References 7 publications
0
13
0
1
Order By: Relevance
“…Median survival was less than 7 months, with 25% of patients living longer than 12 months. Pediatric brain tumor patients having ependymomas and primitive neuroectodermal tumors, in addition to malignant gliomas, have now been safely treated with retrovirus-mediated HSV-TK gene therapy [45]. Clinical trials are currently open for patients with malignant glioma in which retrovirus or recombinant adenovirus is being used to deliver the HSV-TK gene.…”
Section: Gene-directed Enzyme Prodrug ('Suicide Gene') Therapymentioning
confidence: 98%
“…Median survival was less than 7 months, with 25% of patients living longer than 12 months. Pediatric brain tumor patients having ependymomas and primitive neuroectodermal tumors, in addition to malignant gliomas, have now been safely treated with retrovirus-mediated HSV-TK gene therapy [45]. Clinical trials are currently open for patients with malignant glioma in which retrovirus or recombinant adenovirus is being used to deliver the HSV-TK gene.…”
Section: Gene-directed Enzyme Prodrug ('Suicide Gene') Therapymentioning
confidence: 98%
“…A phase I study has demonstrated the safety of in vivo gene transfer in children with poor-risk CNS tumours. Multiple injections of murine vector producing cells are made into the tumour cavity, followed 14 days later by therapy with ganciclovir for two weeks [69]. Although the clinical efficacy of this therapy is as yet unknown, the pre-treatment of human high-grade glioma xenografts with proteases enhances the transfer of adenovirus mediated HSV-TK1/ganciclovir gene therapy [70].…”
Section: Gene Therapy Biological and Gene Therapies Cancer Vaccines mentioning
confidence: 99%
“…Most studies involve implanting VPCs into the cavity of resected tumors. After VPCs implantation, virus diffused into surrounding tissue and ganciclovir was administered; patients were evaluated for survival and toxicity [Izquierdo et al, 1996;Ram et al, 1997;Klatzmann et al, 1998;Shand et al, 1999;Packer et al, 2000;Rainov et al, 2000;Prados et al, 2003]. VPCs in small tumors produced anti-tumor effects [Izquierdo et al, 1996;Ram et al, 1997] and individual case studies showed increased immune response following treatment [Izquierdo et al, 1996;Floeth et al, 2001;Kramm et al, 2002].…”
Section: Conditional Cytotoxicitymentioning
confidence: 99%